An optimal method of DNA silver staining in polyacrylamide gels - Ji, Y.; Qu, Ch.; Cao, B.
A silver staining technique has widely been used to detect DNA fragments with high sensitivity on polyacrylamide gels. The conventional procedure of the silver staining is tedious, which takes about 40-60 min and needs five or six kinds of chemicals and four kinds of solutions. Although our previous improved method reduced several steps, it still needed six kinds of chemicals. The objective of this study was to improve further the existing procedures and develop an optimal method for DNA silver staining on polyacrylamide gels. The novel procedure could be completed with only four chemicals and two solutions within 20 min. The steps of ethanol, acetic acid, and nitric acid precession before silver impregnation have been eliminated and the minimal AgNO3 dose has been used in this up-to-date method. The polyacrylamide gel of the DNA sliver staining displayed a golden yellow and transparent background with high sensitivity. The minimum 0.44 and 3.5 ng of DNA amount could be detected in denaturing and nondenaturing polyacrylamide gel, respectively. This result indicated that our optimal method can save time and cost, and still keep a high sensitivity for DNA staining in polyacrylamide gels.
Keywords: DNA; POLYACRYLAMIDE GEL; SILVER STAINING